The 101¯2 non-cozone twin-twin interactions in Mg: A stability and mobility study using 3-D atomistic simulations. (15th July 2021) - Dang, Khanh; Tomé, Carlos N.; Capolungo, Laurent
Abstract: Due to easy activation of tensile twinning in Mg, multiple 10 1 ¯ 2 twin variants can interact with each other and form twin-twin boundaries over the course of plastic deformation. Previous studies using 2-D settings provide only a partial understanding of these interactions, especially the non-cozone ones. Here, atomistic simulations are used to study the 3-D structural characteristic and evolution of the non-cozone 10 1 ¯ 2 twin-twin junctions. The study reveals the existence of new twin-twin boundaries (TTBs) such as TTBBP and TTBK2, formed after the interaction between the basal prismatic and conjugate twin interfaces with the coherent twin boundary. For both non-cozone twin-twin interactions, the 1 ¯ 2 1 ¯ 2 TTB and its associated twin-twin junctions are found to play a major role in the 10 1 ¯ 2 twin's stability and mobility. Specifically, they promote the growth of the 3-D twin in both the normal and forward directions during the interaction and hinder the detwinning process upon unloading. Graphical abstract: Image, graphical abstract